Effect of Aspirin spraying (Acetyl Salicylic acid) and extract of Eucalyptyus incrassta on growth and yield of Pea (Pisum sativum L.) - وفاق امجد القيسي (Journal of Madenat Alelem University College, 2012)
An experiment was conducted in botanical garden of the Department of biology, College of Education, Ibn Al-Haitham, University of Baghdad during winter season of 2010-2011. The aim of the present study is to investigate the effect of 20 and 40 ppm of Aspirin (Acetyl Salcylic acid) and also the extract of two concentration 5% and 10% of Eucalyptyus incrassta on growth and yield of Pea Pisum sativum L. The results showed that both treatments increased plant height, stem diameter, Crop Growth Rate (CGR), Leaves Growth Rate (RGR), Leaves Surface Area (LAR), Leaf Area Relative (LAR), Leaves Relative Growth Rate (LRGR), number of pods, seeds yield, average seed weight, biological yield, Harvest Index (HI), carbohydrate and protein percentages in seeds and Net Assimilation Rate (NAR), in comparison with the control plants.